Utilization of Palm Fiber and Sikacim Concrete Additive as Additional Materials in Concrete Mixtures Viewed From the Strength of Pulling - Zulkarnain, Fahrizal; Lubis, Delva Enzelya Adila (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2023)
Concrete is an important material used in regional construction. The purpose of this study was to utilize palm fiber as an additive to increase the split tensile strength of concrete. In addition, the sicacim concrete additive is used as a chemical additive in concrete mixtures to produce higher-quality concrete. This study used sicacim concrete additives (0.08% cement) and palm fiber (4%, 5%, and 6% by weight) as cement substitutes. The components of the test object used in this study were vessels with a size of 15 x 30 cm, aged 28 years, and rut values of 60-180 cm—alloy configuration using SNI 03-2834-2000 technique. There are a total of 12 specimens, three for each variation. The finished test is a substantial elasticity test. Based on the research results, the split tensile strength of standard concrete is 3.52 MPa; the split tensile strength of concrete with a mixture of 4% palm fiber and 0.8% sicacim concrete additive is 3.69 MPa; the splitting tensile strength of concrete using a mixture of 5% palm fiber and 0.8% sicacim concrete additive is 4.09 MPa; then the tensile strength of the concrete uses a mixture of 6% palm fiber and 0.8%.ABSTRAKBeton merupakan bahan penting yang digunakan dalam pembangunan daerah. Tujuan penelitian ini adalah memanfaatkan ijuk sebagai bahan tambahan untuk imeningkatkan ikuat itarik ibelah ibeton. iSelain iitu, aditif betonisicacim digunakanisebagaiibahanikimia itambahan idalam campuran betonidalam upaya menghasilkan ibeton iyang ilebih iberkualitas. Dalam penelitian iini, iaditif ibeton isicacim i(0,08% isemen) idan iijuk (4%, 5%, dan 6% berat) digunakan sebagai pengganti semen. Komponen benda uji yang dimanfaatkan pada penelitian ini adalah bejana dengan ukuran yaitu 15 x 30 cm dengan umur 28 tahun, dan nilai rut 60-180 cm. Konfigurasi paduan menggunakan teknik SNI 03-2834-2000. Total ada 12 spesimen, tiga untuk setiap variasi. Uji selesai adalah uji elastisitas substansial. Berdasarkan hasil penelitian, daya tarik belah pada beton normal adalah diangka 3,52 MPa kuat tarik belah beton dengan campuran 4% ijuk dan 0,8% aditif beton sicacim adalah 3,69 MPa; daya tarik belah beton menggunakan bahan campuran 5% ijuk dan 0,8% aditif beton sicacim adalah 4,09 MPa; kemudian daya tarik belah beton menggunakan campuran sebesar 6% ijuk dan 0,8%.